WEB-Based Design of E-Commerce for Small and Medium Enterprises in Bengabing Village - Dewi Wahyuni Dewi; Ekatri Ayuningsih (Sean Institute, 2022)
The development of UMKM has been influenced by the development of information technology and information systems. E-Commerce is one of the technologies that supports the development of UMKM and trade today. The design of this E-Commerce application is designed and built using the waterfall development model. This study aims to develop a sales system for UMKM using information technology and information systems such as E-Commerce. E-Commerce technology is designed and built using website-based applications, making it easier for UMKM users and members to promote UMKM products and their businesses. The main target of using this technology is the UMKM in Bengabing Village, Pegajahan District. Users of this application are administrators who have full rights to application processing and application data, in terms of entering product data. It is hoped that the application of this E-Commerce application can be a medium for developing sales and marketing of UMKM products in Bengabing Village. Users of this application are administrators who have full rights to application processing and application data, in terms of entering product data. It is hoped that the application of this E-Commerce application can be a medium for developing sales and marketing of UMKM products in Bengabing Village. It is hoped that the application of this E-Commerce application can be a medium for developing sales and marketing of UMKM products in Bengabing Village.